2012
DOI: 10.2147/ijn.s32961
|View full text |Cite
|
Sign up to set email alerts
|

Development of a reduction-sensitive diselenide-conjugated oligoethylenimine nanoparticulate system as a gene carrier

Abstract: Background:The reduction-sensitive cationic polymer is a promising nonviral carrier for gene delivery. Until now, disulfide bonds have been the only golden standard for its design. The aim of this research was to develop a novel reduction-responsive cationic polymer as a gene carrier. Methods: Polycationic carriers were synthesized by addition of branched oligoethylenimine 800 Da (OEI 800 ) via an active ester containing diselenide bonds. Disulfide bonds cross-linked with OEI 800 -SS x and monoselenide bonds l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Previous studies showed that the bactericidal effects of honey were partly, if not entirely, due to its acidity, high osmolality, and H 2 O 2 content [41], [42]. These characteristics could also be cytotoxic to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the bactericidal effects of honey were partly, if not entirely, due to its acidity, high osmolality, and H 2 O 2 content [41], [42]. These characteristics could also be cytotoxic to cells.…”
Section: Discussionmentioning
confidence: 99%
“…There are materials that can respond to both oxidation and reduction triggers, which are incorporated into responsive polymers, e.g., diselenides with chemical structure like those of disulfides [29]. Diselenides allows for alternative triggers within nano-biotechnology applications [30].…”
Section: Redox-sensitive Polymersmentioning
confidence: 99%
“…Di-(1-hydroxyethylene) diselenide was synthesized according to the reported method with some modifications [15]. In brief, 2.30 g (30 mmol) Se powder was added into a two-necked flask and dispersed in 15 mL water under nitrogen atmosphere.…”
Section: Synthesis Of Di-(1-hydroxyethylene) Diselenidementioning
confidence: 99%